Digital Game Addiction: A Study On High School Students in Bulanık - Alkan, Feryat (Fırat University, 2025)
This study aims to investigate digital game addiction among high school students in Muş. The global proliferation of the Internet has led to a significant increase in computer usage rates and the number of digital platform users. Concurrently, shrinking physical playgrounds, growing environmental safety concerns, and rapid advancements in digital media tools have collectively shifted children's preferences from physical to digital spaces. This change means child are now choosing to spend their time on the internet, social media, and digital gaming platforms rather than engaging with friends outdoors. Digital gaming platforms have emerged as a significant alternative to real-life interactions, and the increasing time spent on these platforms has elevated the risk of addiction. Using a quantitative research method, data for this study were collected through a "Personal Information Form" designed by the researchers and a validated and reliable scale developed by Hazar and Hazar (2017). The research involved 405 students across 5 high schools in Bulanık district, Muş province. Analysis of the collected data focused on key aspects of addiction, including difficulties in focusing, procrastination behavior, negative projections, and emotional changes experienced by the students.

Bu çalışmanın amacı Muş'taki lise öğrencileri arasında dijital oyun bağımlılığını İncelemektir. İnternetin küresel ölçekte yaygınlaşması, bilgisayar kullanım oranlarında ve dijital platform kullanıcı sayılarında önemli bir artışı beraberinde getirmektedir. Aynı zamanda, fiziksel oyun alanlarının daralması, çevresel güvenlik kaygılarının artması ve dijital medya araçlarındaki hızlı gelişmeler, çocukların tercihlerini fiziksel alanlardan dijital alanlara kaydırmıştır. Bu değişim, çocukların artık dışarıda arkadaşlarıyla vakit geçirmek yerine zamanlarını internet, sosyal medya ve dijital oyun platformlarında geçirmeyi tercih ettikleri anlamına gelmektedir. Dijital oyun platformları gerçek hayattaki etkileşimlere önemli bir alternatif olarak ortaya çıkmıştır ve bu platformlarda geçirilen sürenin artması bağımlılık riskini artırmıştır. Nicel bir araştırma yöntemi kullanılan bu çalışma için veriler, araştırmacılar tarafından tasarlanan bir "Kişisel Bilgi Formu" ve Hazar ve Hazar (2017) tarafından geliştirilen, geçerliliği ve güvenilirliği kanıtlanmış bir ölçek aracılığıyla toplanmıştır. Araştırmaya Muş ili Bulanık ilçesindeki 5 liseden 405 öğrenci katılmıştır. Toplanan verilerin analizi, odaklanma güçlüğü, erteleme davranışı, olumsuz projeksiyonlar ve öğrencilerin yaşadığı duygusal değişiklikler de dahil olmak üzere bağımlılığın temel yönlerine odaklanmıştır.
Dijital Oyun Bağımlılığı: Bulanık Lise Öğrencileri Üzerine Bir Araştırma
Keywords: Screen and Media Culture; Ekran ve Medya Kültürü